A global view of pulmonary hypertension. Issue 4 (April 2016) - Hoeper, Marius M; Humbert, Marc; Souza, Rogerio; Idrees, Majdy; Kawut, Steven M; Sliwa-Hahnle, Karen; Jing, Zhi-Cheng; Gibbs, J Simon R
Summary: Pulmonary hypertension is a substantial global health issue. All age groups are affected with rapidly growing importance in elderly people, particularly in countries with ageing populations. Present estimates suggest a pulmonary hypertension prevalence of about 1% of the global population, which increases up to 10% in individuals aged more than 65 years. In almost all parts of the world, left-sided heart and lung diseases have become the most frequent causes of pulmonary hypertension. About 80% of affected patients live in developing countries, where pulmonary hypertension is frequently associated with congenital heart disease and various infectious disorders, including schistosomiasis, HIV, and rheumatic heart disease. These forms of pulmonary hypertension occur predominantly in those younger than 65 years. Independently of the underlying disease, the development of pulmonary hypertension is associated with clinical deterioration and a substantially increased mortality risk. Global research efforts are needed to establish preventive strategies and treatments for the various types of pulmonary hypertension.